Avaliação do CA2+ intracelular como um mecanismo contribuidor para a diminuição da contração vascular durante a SIRS - Nonato, Arthur Oliveira (2015)
Sepsis is defined as a systemic inflammatory response to infection, featuring a progressive process of tissue injury where multiple organ dysfunction is its most severe expression. Among them, the involvement of the vascular smooth muscle cells (VSMC) is one of offering more life-threatening, since reduced vascular contraction causes a serious state of hypotension. The increased concentration of intracellular calcium (Ca2+) is a determining factor for multiple cells to perform their functions, including VSMC. It is known that the increase in cytoplasmic Ca2+ concentration favors the contraction of VSMC. The stromal interaction molecule (STIM1), functions as an intracellular Ca2+ sensor, which together with another protein called Orai1 form an uptake of extracellular Ca2+ through to the interior of VSMC. Therefore, we hypothesized that the hyporesponsiveness to vasoconstrictors observed during sepsis is mediated by smaller intracellular Ca2+ stores, due disturbances in the STIM/Orai signaling pathway. Male Wistar rats were divided into two groups where the first received an injection of saline, and the second an injection of lipopolysaccharide (LPS, i.p.; 10 mg/kg). The experiments were performed 24 hours after induction of endotoxemia. The results showed that this experimental model of endotoxemia presents various aspects compatible with sepsis, such as a decrease in systolic blood pressure, increased heart rate, neutrophils’ migration into the peritoneal cavity and elevated ALT levels. Hyporeactivity to contractile agents such as PE and KCL; decreased contractile response d to Ca2+; reduced contraction during the Ca2+ loading period and lower intracellular Ca2+ stores were observed in second-order mesenteric arteries from endotoxemic rats. Additionally, decreased expression Orai1, but not STIM1, were found in resistance mesenteric arteries. During Endotoxemia, Ca2+ homeostase is disrupted in VSMC, favoring decreased Ca2+ influx, smaller concentrations of Ca2+ in the sarcoplasmic reticulum, contributing to vascular hyporeactivity to contractile agents.